Two scenes from the Nueva Corónica and good government on the confession of indigenous people: Early sacramental iconography in viceregal Peru - Velezmoro-Montes, Víctor (2011)
This article studies two representive images from the Nueva Corónica y buen gobierno, written by the Andean chronicler Felipe Guaman Poma de Ayala (c. 1615). These drawings depict how the Catholic Sacrament of Penance and Reconciliation was administered to indigenous people within the Viceroyalty of Peru. The scenes are connected to the traditional iconography of sacraments developed within Spanish America, especially those techniques and methods developed by Franciscans within the Americas. This is especially the case when these images are compared as a point of reference with the manuals and documents produced from the Third Council of Lima (1582-1583). However, and despite these obvious connections, this analysis emphasizes the uniqueness of Guaman Poma´s drawings for their novel techniques of composition as a so called "imagen testimonial" (testimonial image) as well as the message that they convey, which departs from information regarding religious conversion in order to subtly complain about religious and civil governance within the Viceroyalty of Peru.